Effectiveness of online communication skills training for cancer and palliative care health professionals: A systematic review. Issue 9 (28th April 2021) - Berg, Melissa N.; Ngune, Irene; Schofield, Penelope; Grech, Lisa; Juraskova, Ilona; Strasser, Michelle; Butt, Zoe; Halkett, Georgia K.B.
Abstract: Objective: To determine the reported effect of online communication skills training (CST) on health professional (HP) communication skills and patient care outcomes in cancer and palliative care. Methods: Primary research published in English between January 2003 and April 2019 was identified in bibliographic databases including Medline, Embase and Proquest (Prospero: CRD42018088681). An integrated mixed‐method approach included studies describing a CST intervention and its effect, for cancer or palliative care HPs, delivered online or blended with an online component. Included studies' outcomes were categorised then findings were stratified by an evaluation framework and synthesised in an effect direction plot. Risk of bias was assessed using Joanna Briggs Institute's tools. Results: Nineteen included studies (five randomised controlled trials, 11 pre‐post, two post‐test and one qualitative study) evaluated a CST intervention (median duration = 3.75 h; range 0.66–96 h) involving 1116 HPs, 422 students and 732 patients. Most interventions taught communication skills for specific scenarios and approximately half were delivered solely online and did not involve role plays. Online CST improved HPs' self‐assessed communication skills (three studies, 215 participants), confidence (four studies, 533 participants), and objective knowledge (five studies, 753 participants). While few studies evaluated patient outcomes, CST may benefit observed communication skills in care settings (two studies, 595 participants). Conclusions: Online CST benefits oncology HPs' subjectively‐reported communication skills and confidence, and objective knowledge. Translation to patient outcomes requires further investigation. The quality of research varied and few studies had a control group. We recommend improvements to study design, evaluation and implementation.